Business Model Canvas: Smart Ceiling Cleaner / Nabihah Ismadi - Ismadi, Nabihah (2020)
A business is a description of the intention of a business operation. The model is used by most researchers and business strategists in explaining organizational value creation, performance and competitive advantage. Business Model Canvas (BMC) consists of nine basic components or building blocks of a business model, which are Key Partnerships, Key Activities, Key Resources, Customer Segments, Value Propositions, Customer Relationships, Channels, Cost Structure And Revenue Streams. The BMC can be used as a mechanism in helping users to map, discuss and invent new business models. In the Figure 1, all the nine components of the business model canvas for the Smart Ceiling Cleaner will be presented. The description of the Business Model using the Business Model Canvas as follows